Comparison of force fields for Alzheimer's A β42: A case study for intrinsically disordered proteins. (26th October 2016) - Carballo‐Pacheco, Martín; Strodel, Birgit
Abstract: Intrinsically disordered proteins are essential for biological processes such as cell signalling, but are also associated to devastating diseases including Alzheimer's disease, Parkinson's disease or type II diabetes. Because of their lack of a stable three‐dimensional structure, molecular dynamics simulations are often used to obtain atomistic details that cannot be observed experimentally. The applicability of molecular dynamics simulations depends on the accuracy of the force field chosen to represent the underlying free energy surface of the system. Here, we use replica exchange molecular dynamics simulations to test five modern force fields, OPLS, AMBER99SB, AMBER99SB*ILDN, AMBER99SBILDN‐NMR and CHARMM22*, in their ability to model Aβ42, an intrinsically disordered peptide associated with Alzheimer's disease, and compare our results to nuclear magnetic resonance (NMR) experimental data. We observe that all force fields except AMBER99SBILDN‐NMR successfully reproduce local NMR observables, with CHARMM22* being slightly better than the other force fields. Abstract : Molecular dynamics simulations are commonly used to complement experimental studies in the understanding of intrinsically disordered proteins. The validity of these simulations depends on the accuracy of the force fields used to model the system. Here, we compare the accuracy of multiple force fields in representing A β 42, an intrinsically disordered protein associated with Alzheimer's disease.